LAND USAGE MONITORING UTILIZING REMOTE SENSING TOOLS - Kolb І.; Kolodii П.; Ryzhov Є.; Urbanavičius, V. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The active development of settlement infrastructure is a crucial aspect of their overall development concept. To facilitate this, visualizing changes by compiling updated plans and populating geospatial databases with relevant information is an essential part of the land management system. Following the decentralization reform in Ukraine, monitoring of recreational landscape changes is now conducted by territorial communities. Consequently, methods for monitoring the recreational land fund and populating geospatial databases require ongoing enhancement. Remote sensing methods are recognized as one of the most effective ways to obtain relevant information about land fund usage. This research applies remote sensing methods to monitor land usage at the municipal level in Solotvyno village, specifically focusing on recreational areas. The study investigates changes resulting from both natural and human impacts, which influence land use infrastructure and future administrative decisions. Solotvyno is a rural settlement located in Transcarpathian region, within the Maramures Basin on the right bank of the Tysa River. It is well-known as a local resort that operates under conditions affected by negative geological phenomena. Resort and recreational activities are conducted on plots that need constant monitoring due to potential dangers to both individuals and infrastructure. Research in this area frequently utilizes remotely obtained data, such as satellite and aerial images. The municipal-level research focuses on an area of 42 km² in Solotvyno, specifically using GIS QGIS based on data from the ESA WorldCover 10 m geoportal. A particular area of interest is the recreational plot located in the southern part of Kunihunda Lake, where economic activities and recreational services have commenced relatively recently. The purpose of this research is to develop a methodology for assessing spatial changes in the Solotvyno resort over the past two years using geoinformation models derived from satellite imagery and UAV aerial photography.